CT-based thermometry: An overview. (June 2014) - Fani, F.; Schena, E.; Saccomandi, P.; Silvestri, S.
Abstract The dependence of computed tomography (CT) values on temperature has been pointed out by several authors since the late 1970s. They emphasised the importance of this phenomenon on the calibration process with water equivalent phantoms of the CT scanners. Few years later the potential of CT thermometry for non-invasive temperature mapping during thermal procedures was investigated. The interest on the employment of this technique during thermal treatments has been recently renewed with the improvement of modern CT scanner performances and with the increased popularity of minimally invasive thermal techniques for cancer treatment. A good thermometry allows avoiding unintended damage of the healthy tissues during the procedure by providing a detailed tissue temperature distribution; therefore, it is recommended in order to achieve good effectiveness of the thermal treatment. Researchers have been working on this issue for more than four decades and different non-invasive solutions have been proposed, i.e., microwave thermal imaging, infrared (IR)-, ultrasound-, magnetic-resonance (MR)-, and CT-based thermometry. This review aims to summarise the essential physics and the currently available data on CT-based thermometry and to elucidate the potential use of this technique during thermal procedures. Background information on measuring principle, an investigation of the performances achieved by this technique and the thermal sensitivity of the CT-number of different organs are provided and discussed.